Functional insights from a surface antigen mRNA-bound proteome - Melo do Nascimento, Larissa; Falk, Franziska; Arnold, Katharina; Papavasiliou, Nina; Clayton, Christine; Erben, Esteban (eLife, 2021)
Trypanosoma brucei is the causative agent of human sleeping sickness. The parasites’ variant surface glycoprotein (VSG) enables them to evade adaptive immunity via antigenic variation. VSG comprises 10% of total cell protein and the high stability of VSG mRNA is essential for trypanosome survival. To determine how VSG mRNA stability is maintained, we used mRNA affinity purification to identify all its associated proteins. CFB2 (cyclin F-box protein 2), an unconventional RNA-binding protein with an F-box domain, was specifically enriched with VSG mRNA. We demonstrate that CFB2 is essential for VSG mRNA stability, describe cis acting elements within the VSG 3'-untranslated region that regulate the interaction, identify trans-acting factors that are present in the VSG messenger ribonucleoprotein particle, and mechanistically explain how CFB2 stabilizes the mRNA of this key pathogenicity factor. Beyond T. brucei, the mRNP purification approach has the potential to supply detailed biological insight into metabolism of relatively abundant mRNAs in any eukaryote.